Income and Democracy : Lipset's Law Revisited - Hoeffler, Anke (IMF Working Papers; Working Paper ;, 2012)
We revisit Lipset's law, which posits a positive and significant relationship between income and democracy. Using dynamic and heterogeneous panel data estimation techniques, we find a significant and negative relationship between income and democracy: higher/lower incomes per capita hinder/trigger democratization. Decomposing overall income per capita into its resource and non-resource components, we find that the coefficient on the latter is positive and significant while that on the former is significant but negative, indicating that the role of resource income is central to the result.